REKONSTRUKSI PENGADILAN ANAK DI INDONESIA (Suatu Orientasi Kearah Restorative Justice) - Loso . (LPPM Universitas Pekalongan, 2011)
Act no. 3 / 1997 on cildren justice, there are several weaknesses, both substantive as well as implementation. Based on the literature search results can be obtained a description of current courts child. The weakness of the substantive law the court the child does not regulate the diversion, whereas the current implementation of the court gives the child the negative impact of stigma on children's self how actors delinquency. Restorative justice model is one model of juvenile justice, in order to protect children in order to avoid the psychic trauma and label / stamp of former criminals. The main purpose of the restorative justice model is the improvement of wound suffered by the victim, perpetrator confession against injury caused by his actions and conciliation and reconciliation among victim, offender and community.